Improvement in thermal conductivity of through-plane aligned boron nitride/silicone rubber composites. (5th March 2019) - Xue, Yang; Li, Xiaofei; Wang, Haosheng; Zhao, Feng; Zhang, Donghai; Chen, Yunfa
Abstract: Effective heat dissipation has become a critical issue for electronic devices. In this study, the silicone rubber (SR)/vertically aligned boron nitride (BN) composites were prepared and the thermal conductivity of the composites was systematically investigated. The vertically aligned BNs constructed effective vertical thermal conductive pathways in the SR matrix, and the SR/ABN composites exhibited much higher through-plane thermal conductivity compared to the non-orientated SR/BN composite. The through-plane thermal conductivity of SR/ABN150 reached 5.4 W m −1  K −1, which was ~6.3 and ~33 times higher than those of SR/BN150 and pure SR, respectively. In addition, the surface thermal infrared analysis also indicates that the vertically aligned SR/ABN composites possess excellent heat transfer capacity during the heating and cooling processes. The obtained results exhibit the potential for the design and preparation of thermal interface materials (TIMs) with high through-plane thermal conductivity to be applied in thermal conductive and electrical insulating field. Graphical abstract: Unlabelled Image Highlights: Through-plane aligned boron nitrides were constructed in silicone rubber matrix. High through-plane thermal conductivity of silicone rubber composites was obtained. Excellent heat dissipation and good electrical insulation were achieved for silicone rubber/aligned boron nitride composites.